THE MEDIATION ROLE OF INTERNAL CONTROL IMPLEMENTATION IN VILLAGE FINANCIAL ACCOUNTABILITY PERFORMANCE - Ietje Nazaruddin; Nisa Nirmala; Siti Fatimah; Ifa Ratifah (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2023)
This study aims to examine the role of internal control implementation as a mediating variable in the relationship between financial knowledge and public participation in the village's financial accountability performance. This research used a questionnaire. Then, the hypotheses were tested utilizing Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showcased that the internal control implementation mediated the relationship between financial knowledge and public participation in the village's financial accountability performance. Further, this study provides practical implications for the government to increase the actualization of the internal control implementation in village financial management.